STRUCTURAL AND ELECTROPHYSIOLOGICAL PREDICTORS OF A PAROXYSM OF ATRIAL FIBRILLATION - B. G. Iskenderov; F. K. Rahmatullov (Российский кардиологический журнал)
We have studied the nature of structural and electrophysiological changes in the heart in various forms of paroxysmal atrial fibrillation (PAF) to determine predictors of an onset and relapse. We have studied 438 patients with PAF, including 68 with the first paroxysm, 92 with rare and 278 with frequent PAF. All patients underwent echocardiography, transesophageal electrophysiology study and Holter monitoring. We have revealed a reliable and appropriate increase in left atrium size, atrium / ventricle ratio, and also decreased frequency threshold of arhythmia induction, left atrium effective refractory period, increased duration of an induced paroxysm and maximal atrial response compared to the control group and as PAF progresses. Regardless of PAF severity a high correlation was established between left atrium size and electrophysiological parameters characterizing atrial arrythmogenic “readiness”, which underlines the provoking role of left atrium dilation.